Phantom Vibration Syndrome Sebagai Dampak Dari Penggunaan Smartphone Yang Berlebihan Pada Remaja - Annisa Mulya Kartini, Baiq (Jurnal Syntax Fusion, 2022)
Smartphone devices have become unbeatable in people's lives because they provide various facilities for finding information, communicating, as a media for learning and entertainment. Besides many benefits of smartphones, excessive use of smartphones has several negative impacts, one of them is phantom vibration syndrome. Phantom vibration syndrome is a common type of hallucination reported by smartphone users in the general population. This syndrome is caused by overuse of smartphones, which feel as if their smartphone is vibrating but is not. The highest population in smartphone use is the age group of 18 to 34 years old. The factors that cause PVS are work, place on the smartphone, age, frequency of using per day and frequency using in vibrate mode. Symptoms that can occur are anxiety and fear. Phantom vibration syndrome has a high prevalence, so early treatment is needed to prevent complications